Flower-like MoS2 on graphitic carbon nitride for enhanced photocatalytic and electrochemical hydrogen evolutions - Liu, Y.; Xu, X.; Zhang, J.; Zhang, H.; Tian, W.; Li, X.; Tade, Moses; Sun, Hongqi; Wang, Shaobin (Elsevier BV, 2018)
Design of highly efficient catalysts has already been a challenge in the exploration of renewable energies based on nanotechnologies. Herein, a feasible strategy of three-dimensional (3D)/two-dimensional (2D) nanojunctions was employed to achieve a prominently enhanced activity in both solar hydrogen evolution and electrochemical hydrogen generation from water splitting. Flower-like MoS2nanoparticles with thin-layers were fabricated using a one-pot hydrothermal process and were further attached to g-C3N4nanosheets via their (002) crystal planes to form an intimate face-to-face contact. The hybrid catalysts exhibited a red-shift to the visible light region with an enhanced absorption capacity. At the optimal loading of 0.5 wt% MoS2, MoS2/g-C3N4exhibited the highest photocatalytic H2evolution rate of 867.6 µmol h-1g-1under simulated sunlight irradiations, which is 2.8 times as high as that of pure g-C3N4. Furthermore, the average photocatalytic H2evolution rate was elevated to ca. 5 times as high as that of pure g-C3N4under visible light irradiations. The synergistic effect responsible for the enhanced HER (hydrogen evolution reaction) performance might be originated from the intimate interface between the light-harvesting g-C3N4and MoS2as the active sites with the decreased overpotential, lowered charge-transfer resistance and increased electrical conductivity, leading to a more efficient charge separation and a higher reductive potential. In addition, the lower overpotential and smaller Tafel slope on 0.5 wt% MoS2/g-C3N4lead to the enhancement of electrochemical HER performance compared to pure g-C3N4. This work provides a feasible protocol for rational design of highly efficient HER electrocatalysts and photocatalysts towards future energy innovation.